2020
DOI: 10.1111/ijac.13487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the sintering temperature on microstructure and properties of Al2O3–Cu–Ni hybrid composites obtained by PPS

Abstract: In the present research, the influence of sintering temperature on the microstructure and properties of Al2O3–Cu–Ni hybrid composites prepared by the Pulse Plasma Sintering (PPS) technique were described. In this research, three temperatures have been selected: 1250°C, 1300°C, and 1350°C. SEM observations were carried out to determine the distribution of the metallic phase in the composite depending on the sintering temperature. The conducted experiments and microscopic observations enabled a better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…We observed that the SiO 2 peak positions are following the literature 43,44,45 . The α‐alumina phase comes from the powder Al 2 O 3 , which is in agreement with the results found in the literature 46,47,48 . We only noticed the presence of the α‐alumina phase in the sintered tape, considering that SiO 2 served as a flux to reduce the sintering temperature 49,50 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the SiO 2 peak positions are following the literature 43,44,45 . The α‐alumina phase comes from the powder Al 2 O 3 , which is in agreement with the results found in the literature 46,47,48 . We only noticed the presence of the α‐alumina phase in the sintered tape, considering that SiO 2 served as a flux to reduce the sintering temperature 49,50 …”
Section: Resultssupporting
confidence: 90%
“…43,44,45 The α-alumina phase comes from the powder Al 2 O 3 , which is in agreement with the results found in the literature. 46,47,48 We only noticed the presence of the α-alumina phase in the sintered tape, considering that SiO 2 served as a flux to reduce the sintering temperature. 49,50 Figure 2B shows a representative SEM image taken from the SCBA waste.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, as mentioned in the Introduction, the temperature of consolidation achieved in the PPS process is higher than in the traditional sintering method [ 38 , 39 ]. Because of that, 1500 °C was the higher applied temperature of the process.…”
Section: Methodsmentioning
confidence: 99%
“…In this technique, the material was heated by electric pulses generated periodically by a discharged capacitor battery and, at the same time, subjected to uniaxial pressing. The application of a capacitor battery as a source of electrical energy allows the electric pulses to be produced periodically over several hundred microseconds and a current intensity of about 100 kA [ 38 , 39 ]. Through the short duration of the electric pulse related to the time interval between the individual pulses, the temperature achieved during the pulse is higher than that stabilized during the traditional sintering method [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation